Non-Animal Technologies to Study and Target the Tumour Vasculature and Angiogenesis - Elisabetta Ferrero; Jonas Hue; Marina Ferrarini; Lorenzo Veschini (Organoids, 2025)
Tumour-associated angiogenesis plays a key role at all stages of cancer development and progression by providing a nutrient supply, promoting the creation of protective niches for therapy-resistant cancer stem cells, and supporting the metastatic cascade. Therapeutic strategies aimed at vascular targeting, including vessel disruption and/or normalisation, have yielded promising but inconsistent results, pointing to the need to set up reliable models dissecting the steps of the angiogenic process, as well as the ways to interfere with them, to improve patients’ outcomes while limiting side effects. Murine models have successfully contributed to both translational and pre-clinical cancer research, but they are time-consuming, expensive, and cannot recapitulate the genetic heterogeneity of cancer inside its native microenvironment. Non-animal technologies (NATs) are rapidly emerging as invaluable human-centric tools to reproduce the complex and dynamic tumour ecosystem, particularly the tumour-associated vasculature. In the present review, we summarise the currently available NATs able to mimic the vascular structure and functions with progressively increasing complexity, starting from two-dimensional static cultures to the more sophisticated tri-dimensional dynamic ones, patient-derived cultures, the perfused engineered microvasculature, and in silico models. We emphasise the added value of a “one health” approach to cancer research, including studies on spontaneously occurring tumours in companion animals devoid of the ethical concerns associated with traditional animal studies. The limitations of the present tools regarding broader use in pre-clinical oncology, and their translational potential in terms of new target identification, drug development, and personalised therapy, are also discussed.